Perdagangan Antarpulau Beras di Provinsi Sulawesi Selatan - Susilowati, Sri Hery (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2017)
As the main staple food, rice is a strategic commodity. Rice production is seasonal and varies among regions. On the other hand, demand for rice is relatively continuous over time throughout the country. Given the characteristics of Indonesia as an archipelagic country dominated by marine areas, inter-island rice trade is a way of bridging the distribution of rice production supply from surplus areas to those deficit one. The study aims to analyze the inter-island rice trade in South Sulawesi including dynamics of inter-island rice trade in the last two decades, distribution of rice trade, and profit margin of each trade actor. Secondary data were collected from various related agencies in Jakarta and South Sulawesi. Primary data were obtained through a survey with farmers and traders as respondents and through group discussions with key informants in 3 regencies/municipality in South Sulawesi Province. Analysis results show that dynamics of inter-island rice traded from South Sulawesi relatively unstable with an increasing trend. Peak shipments occurred in October and the largest share of rice shipments came from Pare-Pare Municipality (60.5%). Jakarta is the main destination for rice delivery with the largest number of shipments (33%), followed by Belawan and Ambon. Considering the characteristics of rice production, consumption and market integration, and importance of rice as an economic and political commodity, inter-rice trade policy can be used as an instrument for stabilizing rice prices. It is necessary to manage spatial and continuous network of marketing activities at national level, i.e. procurement, distribution and storage, according to the rice market size in each region. AbstrakSebagai bahan pangan pokok utama, beras merupakan komoditas strategis. Produksi beras dipengaruhi oleh musim dan terdapat kesenjangan antarwilayah, sebaliknya permintaan beras menyebar sepanjang waktu di seluruh wilayah Indonesia. Dengan karakteristik Indonesia sebagai negara kepulauan yang didominasi oleh wilayah perairan, perdagangan antarpulau beras merupakan cara yang ditempuh dalam menjembatani distribusi pasokan produksi beras dari wilayah surplus dengan permintaan dari wilayah defisit. Tujuan kajian adalah untuk menganalisis keragaan perdagangan antarpulau beras di Provinsi Sulawesi Selatan, meliputi dinamika perdagangan antarpulau beras dalam dua dekade terakhir, distribusi perdagangan beras serta marjin yang diperoleh masing-masing pelaku perdagangan beras di Sulawesi Selatan. Data dan informasi yang dikumpulkan meliputi data sekunder dan data primer. Data sekunder dikumpulkan dari berbagai instansi terkait di Jakarta dan Sulawesi Selatan. Data primer diperoleh melalui pendekatan survei kepada petani dan pedagang dan melalui diskusi kelompok dengan informan kunci di tiga kabupaten di Provinsi Sulawesi Selatan. Hasil analisis menunjukkan dinamika volume beras yang diantarpulaukan dari Provinsi Sulawesi Selatan relatif berfluktiatif namun menunjukkan kecenderungan meningkat. Puncak pengiriman beras antarpulau terjadi pada bulan Oktober dan pangsa pengiriman beras terbesar berasal dari Kabupaten Pare-Pare (60,5%). Jakarta merupakan kota tujuan pengiriman beras utama dengan jumlah pengiriman terbesar, diikuti Belawan dan Ambon. Dengan pertimbangan karakteristik produksi, konsumsi beras, dan pasar beras yang terintegrasi, serta pentingnya beras sebagai komoditas ekonomi dan politik, maka kebijakan perdagangan antarpulau beras dapat digunakan sebagai salah satu instrumen untuk stabilisasi harga beras. Untuk itu diperlukan kebijakan Pemerintah yang mengelola jaringan kegiatan pemasaran antartempat dan antarwaktu (pengadaan, penyaluran dan penyimpanan) secara nasional yang disesuaikan dengan besar kecilnya pasar beras di masing-masing wilayah/daerah.